Pengaruh Model Pembelajaran Kooperatif Problem Solving dalam Meningkatkan Prestasi Belajar pada Mata Pelajaran IPS Terpadu - Syamsul Hadi (Jurnal Pendidik Indonesia (JPIn), 2022)
Educators must better understand the various characteristics of students during the learning process to improve learning achievement, especially in the integrated social studies field. Therefore, educators can change the way of teaching to improve student achievement by using the solution method or Problem Solving. The purpose of this study was to determine the effect of the Problem Solving Cooperative Learning Model in Improving Learning Achievement in Integrated Social Studies Subjects for Class VII in MTs. Attarbiyah Addiniyah Gersik. This type of research is a quasi-experimental design research. The sample in this study was class VII students at MTs. Attarbiyah Addiniyah Gersik totaling 40 people consisting of 20 students VIIa and 20 students VIIb, using a total sampling technique. The instruments used in this research are questionnaires and documentation. This hypothesis test will be carried out with the help of SPSS 21 using the Independent Sample T-Test formula. The results of the study concluded that there was an effect of the Problem Solving Cooperative Learning Model in Improving Learning Achievement in Integrated Social Studies Subjects for Class VII in MTs. Attarbiyah Addiniyah Gersik